Effective transformation of PCDTBT nanorods into nanotubes by polymer melts wetting approach - Aziz, F.; Bakar, N.A.; Bashir, S.; Alhummiany, H.; Bawazeer, T.; Alsenany, N.; Mahmoud, A.; Supangat, A.; Sulaiman, K. (Elsevier, 2017)
In the present study, p-type conducting polymer of poly [N-9′-heptadecanyl-2,7-carbazole-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole)] (PCDTBT) has been explored for nanostructures. A novel approach has been adopted to transform nanorods into nanotubes by altering template-wetting methods. PCDTBT nanorods are fabricated by infiltrating porous alumina template with various solution concentrations of 5, 10 and 15 mg/ml. Upon thermal annealing PCDTBT beyond its melting point, the nanorods are transformed into nanotubes. The morphological and optical investigations reveal that the nanorods prepared with a concentration of 10 mg/ml are longer, denser, well-arranged and red shifted as compared to other nanorods. The PCDTBT nanotubes of the same concentration prepared at 300 °C are found the best among all other nanotubes with improved length, density and alignment as compared to their nanorod counterparts. Furthermore, the optical spectra of the nanotubes demonstrate broad spectral region, augmented absorption intensity and significant red-shift. The changes observed in Raman shift indicate improvement in molecular arrangement of the nanotubes. Optimization of the solution concentration and annealing temperature leads to improvement of PCDTBT nanostructures. PCDTBT nanotubes, with better molecular arrangement and broad optical spectrum, can be exploited in the state-of-the-art photovoltaic devices.